The potential for bi-lateral agreements in medical tourism: A qualitative study of stakeholder perspectives from the UK and India - Smith Richard D; Chanda Rupa; Martínez Álvarez Melisa (BMC, 2011)
Abstract Background Globalisation has prompted countries to evaluate their position on trade in health services. However, this is often done from a multi-lateral, rather than a regional or bi-lateral perspective. In a previous review, we concluded that most of the issues raised could be better addressed from a bi-lateral relationship. We report here the results of a qualitative exercise to assess stakeholders' perceptions on the prospects for such a bi-lateral system, and its ability to address concerns associated with medical tourism. Methods 30 semi-structured interviews were carried out with stakeholders, 20 in India and 10 in the UK, to assess their views on the potential offered by a bi-lateral relationship on medical tourism between both countries. Issues discussed include data availability, origin of medical tourists, quality and continuity of care, regulation and litigation, barriers to medical tourism, policy changes needed, and prospects for such a bi-lateral relationship. Results The majority of stakeholders were concerned about the quality of health services patients would receive abroad, regulation and litigation procedures, lack of continuity of care, and the effect of such trade on the healthcare available to the local population in India. However, when considering trade from a bi-lateral point of view, there was disagreement on how these issues would apply. There was further disagreement on the importance of the Diaspora and the validity of the UK's 'rule' that patients should not fly more than three hours to obtain care. Although the opinion on the prospects for an India-UK bi-lateral relationship was varied, there was no consensus on what policy changes would be needed for such a relationship to take place. Conclusions Whilst the literature review previously carried out suggested that a bi-lateral relationship would be best-placed to address the concerns regarding medical tourism, there was scepticism from the analysis provided in this paper based on the over-riding feeling that the political 'cost' involved was likely to be the major impediment. This makes the need for better evidence even more acute, as much of the current policy process could well be based on entrenched ideological positions, rather than secure evidence of impact.